(untitled) (Research, Society and Development, 2022)
Introduction: azithromycin was one of the most employed medications during the beginning of the SARS-CoV2 pandemic, despite the lack of scientific basis for its use treatment of COVID-19. Its uncontrolled adoption has risen as a public health problem, as it promotes the appearance of drug-resistant bacterial strains, making it difficult to effectively treat many bacterial infections. Objective: to understand the implications of bacterial resistance to azithromycin in the treatment of infections in the fight against COVID-19. Methods: we surveyed a total of 38 scientific articles. The inclusion criteria were: studies whose central theme was bacterial resistance to azithromycin in the treatment of bacterioses and azithromycin in the fight against COVID-19, published from 2015 to 2022. Results: the widespread use of antibiotics may act in the selection of bacterial strains which had long held genetic traits for drug resistance, but which, not representing adaptative advantages, did not proliferate in the subsequent lineages. This direct proportionality between the widespread use and bacterial resistance to azithromycin is yet more aggravated in COVID-19 times, when part of the medical community and layman population self-medicates with azithromycin, without a scientific basis that justifies choosing this drug. Conclusion: there is a direct relationship between the indiscriminate use of azithromycin and a potential bacterial resistance to this drug. The appearance of resistant bacteria represents a serious public health problem due to the broad use of azithromycin against several bacterial infections.